Numerical simulation of entrainment of water fragments from the zone of localization of combustion and pyrolysis of forest fuel materials by air flow; AIP Conference Proceedings; Vol. 2135 : Heat and mass transfer in the thermal control system of technical and technological energy equipment (HMTTSC 2019) - Antonov D. V. Dmitry Vladimirovich; Atroshenko Yu. K. Yuliana Konstantinovna; Kopylov N. P. Nikolay Petrovich; Khasanov I. R. Irek Raviljevich (2019, 2019)
Title screen